PERANCANGAN TROLI PANEN BUNGA POTONG GUNA MEMPERMUDAH PEMINDAHAN DARI KEBUN KE TEMPAT SORTIR BUNGA - Adiluhung, Hardy; Zulkarnain, T. (SPACEPRO: Product Design Jurnal, 2023)
The high need of the community to use cutting flowers on various occasions as well as the short harvest period, makes cutting-flower farming very potential to develop. Florikultura is a subsector of horticultural farming. The cultivation of flowers in the region of Cihideung West Bandung is one of the producers of cutting flowers with good productivity, cutting fruit yields have a sufficiently high grade in terms of quality, so it is the trust of merchants as well as lovers of cut flowers, to always buy and buy from the region. The research is aimed at producing ergonomic flower harvester aids that can reduce the risk of injury at work. The research began with the identification of complaints of workers using the Nordic Body Map (NBM), as well as working processes towards production of cut fruit (output) and the level of technical efficiency on enterprises in the crop crop process. The evaluation results are then processed using product design concepts. Data collection techniques are conducted with interviews, as well as factors that have a real influence on productivity and the size of the planted land that influence the quality of the crop and the efficiency of work. Keywords: Design; Flower Cutting; Harvest Assistant; Ergonomic.